Stress-strain state and wear modelling for fuel rod – grid contact - Breslavsky, Dmytro; Palamarchuk, Pavlo; Tolstolutska, Galyna; Altenbach, Holm (National Science Center "Kharkov Institute of Physics and Technology", 2023)
The paper presents an approach for effective solution of the stress-strain state and wear prediction problem for the case of contact between fuel rod and grid surfaces of a nuclear reactor. Boundary-initial value elastic-plastic problem statement, due to the quasi-static character of the forced oscillations, which was approved by eigen frequencies analysis, was reduced to boundary one. The influence of inhomogeneous temperature field and varying pressure in the outer surface of fuel rod’s shell are considered. For this, a sequence of special procedures for searching the most effective ways of numerical simulation with limited computational resources was considered. The method of weighted residuals and the finite difference method were used to solve the problem of nonlinear forced oscillations under periodic loading of the fuel rod, described as beam under bending. The analytical solution for the fuel rod’s shell displacements in thermo-elasticity problem is obtained, approximated for spatial case and added to the general three-dimensional Finite Element model. The same procedure was adopted for the maximum amplitude values of the displacements which were obtained in the geometrically nonlinear beam problem solution. After that the general elastic-plastic contact problem of the interaction between the fuel rod and the grid surfaces was solved, taking into account preliminary obtained stress distributions achieved by temperature and amplitude displacements influence. The theory of plasticity of an isotropic material with isotropic hardening was used as a model. The limits of linear solutions for beam deflections as well as deflection dependencies upon time are demonstrated and analyzed. The numerically obtained distributions of strains and stresses are presented. By use of the obtained maximum stress values an attempt for the wear estimation in contact zone was done and the fuel rod’s operating time without critical wear during the contact with the grid surface was determined. The obtained results may be considered as corresponding to practical operating data.

Представлено підхід до ефективного розв’язання задачі прогнозування напружено-деформованого стану та зношування для випадку контакту поверхонь твелу та трубної дошки ядерного реактора. Початково-крайову пружно-пластичну постановку задачі внаслідок квазістатичного характеру вимушених коливань, який підтверджено аналізом власних частот, приведено до граничної. Розглянуто вплив неоднорідного температурного поля та змінного тиску на зовнішній поверхні оболонки твелу. Для цього було розглянуто послідовність спеціальних процедур для пошуку найбільш ефективних способів чисельного моделювання з обмеженими обчислювальними ресурсами. Методом зважених відхилів і методом скінченних різниць розв'язано задачу про нелінійні вимушені коливання при періодичному навантаженні твелу, що описується як балка при згині. Аналітичний розв’язок для переміщень оболонки твелу в задачі термопружності апроксимовано для просторового випадку та додано до загальної тривимірної моделі МСЕ. Така ж процедура була прийнята для максимальних значень амплітуди переміщень, отриманих у розв’язуванні задачі геометрично нелінійного згину балки. Після цього розв’язано загальну пружно-пластичну контактну задачу взаємодії поверхонь твелу та трубної дошки з урахуванням попередньо отриманих розподілів напружень, обумовлених доданими температурними та амплітудними переміщеннями. Як модель використано теорію пластичності ізотропного матеріалу з ізотропним зміцненням. Продемонстровано та проаналізовано межі лінійних розв’язків для прогинів балки, а також залежності прогину від часу. Наведено чисельно отримані розподіли деформацій і напружень. За отриманими максимальними значеннями напружень була зроблена спроба оцінювання зношування в зоні контакту та визначено час роботи твелу без критичного зносу під час контакту з поверхнею трубної дошки. Отримані результати можливо вважати такими, що відповідають практичним експлуатаційним даним.
Моделювання напружено-деформованого стану та зношування у місці контакту твелу з трубною дошкою
Keywords: stress-strain state; temperature; reactor vessel internals; finite element method; forced oscillations; Galerkin method; напружено-деформований стан; температура; внутрішні конструкції реакторного корпусу; метод скінченних елементів; вимушені коливання; Метод Гальоркіна